FENOMENA KONFLIK PEMBANGUNAN FLYOVER KAWASAN PASAR KEMBANG KOTA SURABAYA - , KENAN ARDITO DWIANGGA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The development of a city is highly influenced by the availability of the city facilities, on of which is a road. The road that is supporting a transportation sector of a city is actually the main challenge in most of the developing city in Indonesia, including Surabaya. The solution regarding the challenge faced is taken immediately by the development of a flyover and it focused on the Area of Pasar Kembang. The flyover development that firstly thought as a solution then become the source of another problem. Bad coordination within the parties and another bureaucracy problem then lead them to the arousal conflict. All in all, detail planning of a project needs to be defined as clearly as possible so that it can be implemented smoothly. Keyword: Conflict, Bureaucracy, Development, Flyover, Surabaya